Village Chicken Production Systems in Rural Africa. Household Food Security and Gender Issues - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
FAO. 1998. 82 pp.ISBN 92 51041601 $20.00 / Euro 9.50FAO Sales and Marketing GroupViale delle Terme di Caracalla, 00100 Rome, Italy.Fax: +39 06 57 05 33 60Email: publications-sales@fao.org